Methodological Foundations of Film Speech Analysis Using Corpora: Technical, Social, and Cultural-National Aspects - Ya. M. Alyunina (Научный диалог, 2024)
The aim of this study is to describe the possibilities and limitations of the corpus approach to the analysis of film subtitles, taking into account their technical, social, and culturalnational features. It offers a review of existing film content corpora accompanied by their critical interpretation, firstly from the perspective of subtitle quality as empirical data for linguistic research, and secondly from the perspective of corpus quality as an environment for quantitative analysis of empirical material. Furthermore, based on established subtitling practices, the author proposes her own viewpoint on subtitles as material for studying film speech, considering technical (line length, screen size adaptation), social (subtitles for the deaf and hard of hearing), and cultural-national (subtitling countries vs dubbing countries) aspects of subtitling in different languages and countries. In the course of the work, it was found that the largest number of subtitles available in open repositories are translated equivalents of cinema speech. It is noted that subtitling is preferred in the USA, UK, India, China, and Japan. The features of subtitling in countries such as Serbia, Finland, and Russia are described. The author concludes that these features are important for the quality of linguistic research on the basis of translated movie speech represented by subtitles.